The Communication Presentation of Barack Obama Public Speaking Style - Kais A. Kadhim; Abdul Mutalib Embong; Huang Wen; Muhamad Khairul Zakaria; Wan Zulkifli Wan Kassim (Lingkar Studi Komunikasi (LISKI), 2023)
The main idea of this research is to analyse the English modals in Obama's speech semantically. The modal auxiliaries selected for analysis include (Will, Would, Can, Could, and Should). All the modal auxiliaries are interpreted based on the framework of Coates’ (1983) semantic clusters. The qualitative method of analysis is applied into this study. The modal auxiliary of ‘can’ signifying possibility functions to evoke positive emotions and connotations in the mind of all the listeners. It highlights the possibilities that are associated with people's hopes and wishes and reminds all citizens to look on the bright side, and the persuasion form is realized through the motivation on the Obama’s speech modal auxiliaries’ words. Keywords: Obama’s, Modality, Function, Speech, Public Speaking